Modulation of intestinal corticotropin-releasing hormone signaling by the herbal preparation STW 5-II: possible mechanisms for irritable bowel syndrome management - Elbadawi, Mohamed; Ammar, Ramy M.; Rabini, Sabine; Klauck, Sabine; Efferth, Thomas (Pharmaceuticals, 2022)
Corticotropin-releasing factor (CRF) mediates stress responses and alters the gut-brain axis, contributing to the pathogenesis of irritable bowel syndrome (IBS), which is recognized by abdominal pain accompanied by bowel habit disturbance. STW 5-II, a mixture of six herbal extracts, is clinically effective in functional dyspepsia and IBS. Here we aimed to establish an organoid-based stress-induced IBS-like model to investigate the mechanisms of action of STW 5-II.
Gesehen am 29.11.2022